Super (a,d)-$mathcalH$-Antimagic Total Selimut pada Graf Shackle Kipas $F_4$ - Azizah, Irma; Dafik, Dafik (Prosiding Seminar Matematika dan Pendidikan Matematik, 2014)
A graph $G(V,E)$ has a $mathcalH$-covering if every edge in $E$ belongs to a subgraph of $G$ isomorphic to $mathcalH$. An $(a,d)$-$mathcalH$-antimagic total covering is a total labeling $lambda$ from $V(G)cup E(G)$ onto the integers ${1,2,3,...,|V(G)cup E(G)|}$ with the property that, for every subgraph $A$ of $G$ isomorphic to $mathcalH$ the $sumA=sum_{vin{V(A)}}lambda{(v)}+ sum_{ein{E(A)}}lambda{(e)}$ forms an arithmetic sequence. A graph that admits such a labeling is called an $(a,d)$-$mathcalH$-antimagic total covering. In addition, if ${lambda{(v)}}_{vinV}={1,...,|V|}$, then the graph is called $mathcalH$-super antimagic graph. In this paper we study a super $(a,d)$-$mathcalH$-antimagic total Covering ofÂ  Shackle of Fan $F_4$.